Assertive Community Treatment for alcohol dependence (ACTAD): study protocol for a randomised controlled trial - Gilburt Helen; Burns Tom; Copello Alex; Coulton Simon; Crawford Michael; Day Ed; Deluca Paolo; Godfrey Christine; Parrott Steve; Rose Abigail K; Sinclair Julia MA; Wright Christine; et al. (Trials, 2012)
Abstract Background Alcohol dependence is a significant and costly problem in the UK yet only 6% of people a year receive treatment. Current service provision based on the treatment of acute episodes of illness and emphasising personal choice and motivation results in a small proportion of these patients engaging with alcohol treatment. There is a need for interventions targeted at the population of alcohol dependent patients who are hard to engage in conventional treatment. Assertive Community Treatment (ACT), a model of care based on assertive outreach, has been used for treating patients with severe mental illnesses and presents a promising avenue for engaging patients with primary alcohol dependence. So far there has been little research on this. Methods/Design In this single blind exploratory randomised controlled trial, a total of 90 alcohol dependent participants will be recruited from community addiction services. After completing a baseline assessment, they will be assigned to one of two conditions: (1) ACT plus care as usual, or (2) care as usual. Those allocated to the ACT plus care as usual will receive the same treatment that is routinely provided by services, plus a trained key worker who will provide ACT. ACT comprises intensive and assertive contact at least once a week, over 50% of contacts in the participant's home or local community, and comprehensive case management across social and health care, for a period of one year. All participants will be followed up at 6 months and 12 months to assess outcome post randomisation. The primary outcome measures will be alcohol consumption: mean drinks per drinking day and percentage of days abstinent measured by the Time Line Follow Back interview. Secondary outcome measures will include severity of alcohol dependence, alcohol related problems, motivation to change, social network involvement, quality of life, therapeutic relationship and service use. Other outcome variables are treatment engagement including completion of assessment, detoxification and aftercare. Discussion Results of this trial will help clarify the potential beneficial effects of ACT for people with alcohol dependence and provide information to design a definitive trial. Trial registration number ISRCTN: ISRCTN22775534